2021
DOI: 10.3389/fcimb.2021.723121
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cell Response Quality Is Related to Parasite Control in an Animal Model of Single and Mixed Chronic Trypanosoma cruzi Infections

Abstract: Chagas disease (ChD) is a chronic infection caused by Trypanosoma cruzi. This highly diverse intracellular parasite is classified into seven genotypes or discrete typing units (DTUs) and they overlap in geographic ranges, vectors, and clinical characteristics. Although studies have suggested that ChD progression is due to a decline in the immune response quality, a direct relationship between T cell responses and disease outcome is still unclear. To investigate the relationship between parasite control and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 116 publications
(185 reference statements)
0
4
0
Order By: Relevance
“…In contrast, infected mice with a high inflammatory infiltrate (Y-infected mice) or high parasitaemia and parasitism (DA/Y-infected mice) showed a CD8 + T cell response distinguished by an increase in late-differentiated cells, a monofunctional response, and enhanced expression of inhibitory receptors. Overall, our results demonstrated that the infection caused by single or mixed T. cruzi infection with different parasite genotypes induce a differential immune CD8 + T cell response quality, which suggest that the quality of CD8 + T cell response might dictate differences in the parasite control and infection outcomes at the chronic T. cruzi stage ( Mateus et al., 2017 ; Mateus et al., 2021 ).…”
Section: Cd8 + T Cell Quality: a Biomarker Of Dise...mentioning
confidence: 65%
See 2 more Smart Citations
“…In contrast, infected mice with a high inflammatory infiltrate (Y-infected mice) or high parasitaemia and parasitism (DA/Y-infected mice) showed a CD8 + T cell response distinguished by an increase in late-differentiated cells, a monofunctional response, and enhanced expression of inhibitory receptors. Overall, our results demonstrated that the infection caused by single or mixed T. cruzi infection with different parasite genotypes induce a differential immune CD8 + T cell response quality, which suggest that the quality of CD8 + T cell response might dictate differences in the parasite control and infection outcomes at the chronic T. cruzi stage ( Mateus et al., 2017 ; Mateus et al., 2021 ).…”
Section: Cd8 + T Cell Quality: a Biomarker Of Dise...mentioning
confidence: 65%
“…Although all parasite DTU’s are known to be circulating in Colombia ( Guhl and Ramirez, 2013 ), parasites belonging to DTU TcI and, to a lesser extent, DTU TcII, have been the ones mainly recovered from patients ( Ramirez et al., 2010 ). In this context, our results from mice chronic infections with DTU TcI (DA), and DTU TcII (Y) strains showed that both parasite strain and type of infection (single or double) influenced parasitemia, parasitism and inflammatory response ( Mateus et al., 2021 ). Therefore, it is possible that parasite DTUs could affect disease outcomes.…”
Section: Perspectivesmentioning
confidence: 88%
See 1 more Smart Citation
“…This pronounced genetic variability allows reinfections by different strains, also known as co-infections, polyparasitism, or mixed infections. Previous studies have described polyparasitism in insect vectors (11,12), human patients (13)(14)(15)(16), experimental infection and treatment effects in animal models (17)(18)(19)(20). At endemic areas, the occurrence of co-infections is estimated between 9 and 57% (14)(15)(16)21).…”
Section: Introductionmentioning
confidence: 99%